IMPLEMENTASI PRINSIP KEADILAN SOSIAL DALAM DISTRIBUSI BANTUAN LANGSUNG TUNAI DESA DI DESA MANGKI KABUPATEN PINRANG (Jurnal Washiyah: Jurnal Kajian Dakwah dah Komunikasi, 2023)
Village Direct Cash Transfer is assistance sourced from village funds in the form of cash distributed to underprivileged communities to help for community welfare, so the distribution must be based on the principle of justice so that the provision of assistance becomes effective. The data collection methods used were observation, interviews, and documentation. This research is qualitative research with a research approach to social welfare disciplines. The results of this study show that the implementation and mechanism of aid distribution through several data collection channels, consolidation and verification, and validation and results, as for the application of social justice principles in the distribution of Village Cash Direct Transfers, namely the Principle of Justice for attention and provision of individual rights, the Principle of Justice for attention and provision of individual rights, the principle of justice of difference (the difference principle) and the affair equality of opportunity and the principle of procedural justice.